(untitled) (Al-Mansour Journal, 2023)
In a rapid changeable and very developing world in financial and economical manifestations ,business organization faced some challenges , these challenges effects in a rigid way on a reliability , accuracy of accounting measurement and for casting a variables which effect in the value of organization will be difficult mission under historical cost approach . Therefore to overcome this problem , a best approach in determine a future accounting measurement of organization value and full disclosure of its assets and liabilities will be a fair value approach . This research will highlight the importance of applying a affair value accounting approach , and acquainting a accounting derivatives in business organization and showing to which extent this will be matching witch Iraqi accounting standards and rules which issues by Iraqi standard committee . Finally suggest and developed a procedure which used in Iraq in this content and encourage the academic research in accounting derivatives under uniform accounting system .